2014
DOI: 10.1139/cjb-2013-0174
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization inPopulusalters the species composition and interactions of root-colonizing fungi: consequences for host plant performance

Abstract: Interactions among plants and soil microbes can significantly influence plant communities, yet we understand little about how hybridization of plant species might alter these interactions. In addition, few studies have explored the effects of different components of soil microbial communities on plant performance. We tested for feedbacks between soil microbes within a Populus hybridizing system using approaches that allowed us to isolate the effects of arbuscular mycorrhizal fungi (AMF) and root endophytes. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 43 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Studies that have directly investigated these questions are rare and have yielded conflicting results. In Populus, Gehring et al (2013) observed that an increase in DSE fungal colonization was correlated with a decrease in AMF colonization. In contrast, Della Monica et al 2015and Wężowicz et al (2017) showed similar rates of AMF colonization in plants co-inoculated with AMF and DSE than those solely inoculated with AMF.…”
mentioning
confidence: 97%
“…Studies that have directly investigated these questions are rare and have yielded conflicting results. In Populus, Gehring et al (2013) observed that an increase in DSE fungal colonization was correlated with a decrease in AMF colonization. In contrast, Della Monica et al 2015and Wężowicz et al (2017) showed similar rates of AMF colonization in plants co-inoculated with AMF and DSE than those solely inoculated with AMF.…”
mentioning
confidence: 97%